Household travel characteristics to healthcare facilities in Ondo State, Nigeria - Omotayo Ben Olugbamila; Samson Ajibola Adeyinka; Lucy Nkeiruka Ugwu; John Taiwo Famutimi; Odunwole Sogbon (Economic and Environmental Studies (E&ES), 2018)
This study investigated the household travel characteristics of health consumers in Ondo State to the available healthcare facilities. The study uses data collected from 1,181 health consumers from forty-two (42) settlements across the three senatorial districts of the State. The findings revealed that while some of the healthcare patrons travelled below 400 meters to get to the nearest healthcare facility, many of them spent more money on trips to reach their healthcare facilities. This shows that the majority of people are ready to patronize any healthcare facility irrespective of the distance and cost. The further analysis revealed that distance, travel time, cost of transport and travel mode are significant to the utilization of healthcare facilities. To this end, more healthcare facilities should be provided and located closer to people within shortest possible distance, especially in Ondo North and Ondo South senatorial districts.
Keywords: I10; I18; L99; R49; 330; accessibility; distance; healthcare facilities and health consumers